The Influence of Bilingualism and Language Attitudes on Language Choice in Multilingual Communities in a West Javan University - Poetri AL-Viany Maqfirah; Sabil Mokodenseho (Eastasouth Institute, 2023)
This study looks into the intricate relationships that exist between language attitudes, language choices, and bilingualism in a West Javan university. There are 250 participants in the study, who are a varied cross-section of the academic community. Analysis of demographic data shows that the distribution is equal for both genders and age groups. The prevalence of Bahasa Indonesia, Sundanese, Javanese, other regional languages, and English is shown via linguistic background investigation, demonstrating the linguistic diversity present in the university community. The survey also explores academic levels, with undergraduate students making up the majority of participants. Results of the poll show that a significant portion of individuals were multilingual, speaking two or more languages. Sundanese & Bahasa Indonesia, Javanese & English, and Bahasa Indonesia & English are common language partnerships. Language attitudes that are positive toward multilingualism and native languages vary depending on one's linguistic background. Language preferences for Bahasa Indonesia and English are evident in both formal and casual contexts. Significant connections between bilingualism, linguistic attitudes, and linguistic preferences are revealed by correlation analysis.